2007
DOI: 10.1016/j.brainres.2007.07.061
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to screening for new neuroprotective compounds for the treatment of stroke

Abstract: Despite the significant advances that have been made in understanding the pathophysiology of cerebral ischemia on the cellular and molecular level, only one drug, the thrombolytic tissue plasminogen activator (rt-PA), is approved by the FDA for use in patients with acute ischemic stroke. Therefore, there is a critical need for additional safe and effective treatments for stroke. In order to identify novel compounds that might be effective, we have developed a cell culture-based assay with death being an endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 54 publications
(75 reference statements)
5
121
1
Order By: Relevance
“…Not only did fisetin prevent cell death but it stood out among the flavonoids tested as being able to maintain ATP levels in the presence of IAA. Further studies in the rabbit small clot embolism model of stroke demonstrated that fisetin could significantly improve the behavioral outcome when administered 5 min after the initiation of an embolic stroke [58]. Consistent with our animal data, fisetin was also shown to reduce ischemic damage and infarct volume in the permanent focal middle cerebral artery occlusion model of stroke in rats [73].…”
Section: Mechanism Of Actionsupporting
confidence: 86%
See 3 more Smart Citations
“…Not only did fisetin prevent cell death but it stood out among the flavonoids tested as being able to maintain ATP levels in the presence of IAA. Further studies in the rabbit small clot embolism model of stroke demonstrated that fisetin could significantly improve the behavioral outcome when administered 5 min after the initiation of an embolic stroke [58]. Consistent with our animal data, fisetin was also shown to reduce ischemic damage and infarct volume in the permanent focal middle cerebral artery occlusion model of stroke in rats [73].…”
Section: Mechanism Of Actionsupporting
confidence: 86%
“…Furthermore, following a single intraperitoneal injection, fisetin was detected in the brains of rats and this correlated with a significant reduction in cerebral damage in a stroke model [73]. Similarly, we have seen significant protection in a rabbit stroke model following intravenous injection of fisetin [58] and we found that oral administration of fisetin could enhance learning and memory in mice [57]. Thus, fisetin is able to affect neuronal function in vivo.…”
Section: Metabolism Of Fisetinsupporting
confidence: 65%
See 2 more Smart Citations
“…However, hydrogen, different from normal antioxidants, is electrically neutral and much smaller, so it could easily penetrate blood-testis barrier and enter cells and organelles such as the nucleus and mitochondria. (2) Hydrogen is able to selectively reduce the hydroxyl radical and ONOO-, the most cytotoxic chemicals of ROS, and effectively protect cells, but does not react with other ROS, which possess physiological roles [27].…”
Section: Discussionmentioning
confidence: 99%